Signals of the QCD phase transition in core collapse supernovae - microphysical input and implications on the supernova dynamics - Fischer, Tobias; Sagert, Irina; Hempel, Matthias; Pagliara, Giuseppe; Schaffner-Bielich, Jürgen; Liebendörfer, M. (Classical and quantum gravity, 2010)
In contrast to heavy ion collisions, matter in astrophysical systems such as neutron stars, compact star mergers and supernova environments can be highly isospin asymmetric. We focus on core collapse supernova matter where temperatures reach tens of MeV. Both conditions, the high temperatures and isospin asymmetry, can favour an early phase transition to quark matter already close to nuclear saturation density. We examine the QCD phase transition during the early postbounce phase of core collapse supernovae. We discuss the microphysical input, i.e. the modelling of the phase transition to strange quark matter, and the consequences on the dynamical evolution as well as the observable neutrino signal from the phase transition. The equation of state for strange quark matter is based on the MIT bag model. The phase transition is constructed applying the Gibbs criterion which results in an extended coexistence region in the phase diagram between the hadronic and the quark phases, i.e. the mixed phase. The supernovae are simulated via general relativistic radiation hydrodynamics based on three-flavour Boltzmann neutrino transport in spherical symmetry. The dynamical evolution of the phase transition to quark matter is determined by an adiabatic collapse due to the softening of the equation of state in the mixed phase. The equation of state for the pure quark phase stiffens again which causes the collapse to halt and a shock wave forms at the boundary between the mixed and the pure hadronic phases. This shock accelerates and launches an explosion, which releases a burst of neutrinos dominated by electron anti-neutrinos due to the lifted degeneracy of the shock-heated hadronic material.
Gesehen am 08.05.2023